2012
DOI: 10.1021/mz300386g
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Polydispersity in Chemical Composition and Monomer Sequence Distribution in Random Copolymers Prepared by Postpolymerization Modification of Homopolymers

Abstract: We report on establishing the polydispersity in chemical composition (PCC) and polydispersity in monomer sequence distribution (PMSD) in random copolymers of poly(styrene-co-4-bromostyrene) (PBr x S), where x = (0.385 ± 0.035) is the mole fraction of the 4bromostyrene units (4-BrS), prepared by electrophilic substitution of bromine in the para-position of the phenyl ring of the parent polystyrene. Upon fixing the total number of repeating units, we tune the distribution of styrene and 4-BrS segments in PBr x S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Several experimental , and kinetic modeling studies , were reported in which the influence of copolymerization conditions on the monomer sequence and, hence, the copolymer properties was investigated in CRP processes. It was shown that copolymer composition drift can exist under both homogeneous and heterogeneous ATRP batch conditions, ,, and a semibatch approach can be beneficial. ,,, For example, simulations based on the method of moments and the kinetic Monte Carlo (kMC) technique showed that semibatch ATRP allows to optimize the comonomer feed rates to achieve a desired overall copolymer composition. , However, in these modeling studies the copolymer composition was not explicitly tracked.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental , and kinetic modeling studies , were reported in which the influence of copolymerization conditions on the monomer sequence and, hence, the copolymer properties was investigated in CRP processes. It was shown that copolymer composition drift can exist under both homogeneous and heterogeneous ATRP batch conditions, ,, and a semibatch approach can be beneficial. ,,, For example, simulations based on the method of moments and the kinetic Monte Carlo (kMC) technique showed that semibatch ATRP allows to optimize the comonomer feed rates to achieve a desired overall copolymer composition. , However, in these modeling studies the copolymer composition was not explicitly tracked.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the polymer science landscape to access architecturally tailored and sequence-specified macromolecules to acquire enhanced properties. Structurally controlled polymers are of widespread importance across many diverse fields, from drug delivery to photovoltaics and microlithography .…”
mentioning
confidence: 99%
“…The sequence distribution of the PBCCTs was also analyzed using 13 C NMR spectroscopy, as shown in Figures S2 and S3, to determine the microstructure of the backbone, such as the degree of randomness and number-average sequence length. , As shown in Table S1, the molar fractions ( f ) of each dyad were obtained by integrating the relative peak areas. The number-average sequence length ( L ) and the degree of randomness ( R ) of these dyads were calculated based on the amounts of carbonate and terephthalate according to previously published equations. , The microstructure of the resulting polymers, i.e., whether they are random, block-like, or alternating structures, influences the materials properties significantly. , As such, the degrees of randomness based on carbonate ( R C* ) were calculated and found to be 1.09 (PBCCT10), 0.92 (PBCCT20), 0.96 (PBCCT30), 0.96 (PBCCT40), and 0.98 (PBCCT50), and the degrees of randomness values based on terephthalate ( R T ) were 1.16 (PBCCT10), 1.01 (PBCCT20), 0.99 (PBCCT30), 0.98 (PBCCT40), and 0.95 (PBCCT50). In the case of a random copolymer, R takes a value of 1, while alternate copolymer and block copolymer take values of 2 and near 0, respectively. , Therefore, the R values of all the synthesized PBCCTs close to 1 suggests that they were random copolymers with a uniformly distributed sequence of monomers.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 The microstructure of the resulting polymers, i.e., whether they are random, block-like, or alternating structures, influences the materials properties significantly. 41,42 As such, the degrees of randomness based on carbonate (R C* ) were calculated and found to be 1.09 (PBCCT10), 0.92 (PBCCT20), 0.96 (PBCCT30), 0.96 (PBCCT40), and 0.98 (PBCCT50), and the degrees of randomness values based on terephthalate (R T ) were 1.16 (PBCCT10), 1.01 (PBCCT20), 0.99 (PBCCT30), 0.98 (PBCCT40), and 0.95 (PBCCT50). In the case of a random copolymer, R takes a value of 1, while alternate copolymer and block copolymer take values of 2 and near 0, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%